The cyclic gene Hes1 contributes to diverse differentiation responses of embryonic stem cells - Kobayashi, Taeko (Cold Spring Harbor Laboratory Press, 2009)
Stem cells do not all respond the same way, but the mechanisms underlying this heterogeneity are not well understood. Here, we found that expression of Hes1 and its downstream genes oscillate in mouse embryonic stem (ES) cells. Those expressing low and high levels of Hes1 tended to differentiate into neural and mesodermal cells, respectively. Furthermore, inactivation of Hes1 facilitated neural differentiation more uniformly at earlier time. Thus, Hes1-null ES cells display less heterogeneity in both the differentiation timing and fate choice, suggesting that the cyclic gene Hes1 contributes to heterogeneous responses of ES cells even under the same environmental conditions.